Work-Related Skin Diseases among Workers in the Sewing Section at PT. X Shoe Company in West Java - Hendra, Hendra; Nirwana, Eva; Isahak, Marzuki (Kesmas, 2018)
Occupational skin diseases are the most common work-related diseases in many countries. Shoe industry workers are potential to be affected by work-related skin diseases (WRSDs). This study aimed to analyze the risk factors associated with WRSDs among workers in the sewing section at a shoe company in West Java. A total of 477 workers were examined and interviewed using the modified Nordic Occupational Skin Questionnaire-2002/LONG from May 2016 to July 2016. Chi-square test and logistic regression were used to analyze the risk factors related to WRSDs. The results showed that 57.7% of the workers suffered from WRSDs. Most of the workers (71.7%) did not wear gloves while working; however, they washed their hands adequately at work (67.1%). Multivariate analysis indicated that a term of work, allergy records, organic dust exposure and duration of exposure per day, handwashing habits, and use of gloves while working were significant to WRSDs. Having allergy records and not wearing gloves were the two dominant factors associated with WRSDs (odds ratio: 6.743 and 6.224, respectively). Understanding the importance of using chemical protective gloves while working and washing hands with running water are essential for the proper implementation of protective measures to ensure worker's safety and health.